Endometrial proteomic profile of patients with repeated implantation failure - Yang, Jing; Wang, Linlin; Ma, Jingwen; Diao, Lianghui; Chen, Jiao; Cheng, Yanxiang; Yang, Jing; Li, Longfei (Frontiers in Endocrinology, 2023)
Successful embryo implantation is the initiate step of pregnancy, relies on not only the high quality of embryo, but also the synergistic developed healthy endometrium. Characterization and identification of biomarkers for the receptive endometrium is believed as an effective way to increasing the probability of successful embryo implantation. To this end, isobaric tag for relative and absolute quantitation (iTRAQ)-based proteomics analysis was employed in the present study to identify the differentially expressed proteins (DEPs) of endometrium from patients with repeated implantation failure (RIF) compared with those from fertile controls. Primarily, two hundred and sixty-three DEPs were identified from iTRAQ, that mainly included proteins with multiple bioactivities such as protein translation, mitochondrial function, oxidoreductase activity, fatty acid and amino acid metabolism. Later, four potential biomarkers for receptive endometrium named TPPP3, S100A13, HSD17B2 and AZGP1 were verified by western blot and immunohistochemistry staining. Additionally, the expression pattern of TPPP3 and HSD17B2 were further confirmed in decidual and endometrial tissues from other published databases. Totally, this study provides novel evidences that TPPP3 and HSD17B2 may be effective targets for the diagnosis and treatment of unreceptive endometrium and RIF, which are deserved to be further studied.